1997
DOI: 10.1093/brain/120.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the motor hand area to a knob on the precentral gyrus. A new landmark

Abstract: Using functional magnetic resonance imaging (fMRI) we have evaluated the anatomical location of the motor hand area. The segment of the precentral gyrus that most often contained motor hand function was a knob-like structure, that is shaped like an omega or epsilon in the axial plane and like a hook in the sagittal plane. On the cortical surface of cadaver specimens this precentral knob corresponded precisely to the characteristic 'middle knee' of the central sulcus that has been described by various anatomist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
1,156
0
11

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,680 publications
(1,239 citation statements)
references
References 4 publications
54
1,156
0
11
Order By: Relevance
“…Taken together, these findings and the results of the quality assurance (QA) measurement demonstrate a good EPI signal quality and validate our overall setup. The rTMS-induced activation in M1 is localized to the hand knob (14), i.e., to the part of M1 containing the representation of the hand muscles (Fig. 3b, z ϭ 56 and 62).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings and the results of the quality assurance (QA) measurement demonstrate a good EPI signal quality and validate our overall setup. The rTMS-induced activation in M1 is localized to the hand knob (14), i.e., to the part of M1 containing the representation of the hand muscles (Fig. 3b, z ϭ 56 and 62).…”
Section: Discussionmentioning
confidence: 99%
“…In left motor cortex, response changes elicited a signal increase in the middle genu of the left precentral gyrus at the location of the hand motor representation area (Yousry et al, 1997;Fig. 5c).…”
Section: Response Changesmentioning
confidence: 98%
“…We also found that the individual centers of LPMC and SMC are close in proximity, resulting in a large overlapping area between the two regions. It is possible that this overlap is due to the variability inherent in the shape and extent of the central sulcus within (White et al, 1997;Rademacher et al, 2001b;Fesl et al, 2003) and between subjects (White et al, 1997;Yousry et al, 1997;Roland and Zilles, 1998;Moore et al, 2000;Rademacher et al, 2001b).…”
Section: Caudal Limit Of Lpmcmentioning
confidence: 99%